PENGARUH MODEL PEMBELAJARAN CIRC TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS V - Fadilah, Heti; Nurmayani, Nurmayani; Simbolon, Naeklan; Perangin-angin, Laurensia Masri; Sembiring, Masta Marselina (Universitas Negeri Medan, 2024)
This research was carried out with the aim of finding out the effect of the CIRC learning model on reading comprehension skills in class V students at SD Negeri 106456 Bantan Village. This research uses a quantitative pre-experimental approach type one group pretest-posttest design. Researchers use observation, tests, and documentation in collecting data. The subjects in this research were 27 class V students of SD Negeri 106456 Bantan Village, 12 men and 15 women. The low reading comprehension ability of students is the reason researchers conducted this research, this can be seen from the learning achievements of students who have not yet reached the KKM. This is because the learning activities carried out are not optimal. Students just read the text without any activities that enable them to understand the content of the reading. The learning model applied is also monotonous and results in students being less interested. Therefore, researchers will apply the Cooperative Integrated Reading and Composition (CIRC) learning model. The research results show that students' reading comprehension abilities have increased after using the CIRC learning model. This can be seen from the average student pretest score of 49.26 and the average student posttest score of 80.00 after the CIRC learning model was implemented. During the pretest, only 7.4% of students were classified as complete. However, at the time of the posttest, 81.48% of students were classified as complete.Keywords: Reading Comprehension, Cooperative Integrated Reading and Composition (CIRC) Learning Model, Indonesian